Joyce in America : cultural politics and the trials of Ulysses - Segall, Jeffrey (Berkeley : University of California Press, 1993)
When James Joyce's Ulysses was first published in America, it quickly became a dynamic symbol of both modern art and the modern age. Jeffrey Segall skillfully demonstrates how various political, ideological, and religious allegiances influenced the critical reception and eventual canonization of what is perhaps the twentieth century's greatest novel. In re-creating the polemical debates that erupted, Segall provides a dramatic.
Introduction: The Polemics of Our Portraits -- 1. "James Joyce or Socialist Realism?" Marxist Aesthetics and the Problem of Ulysses -- 2. "Kulturbolschewismus Is Here": Joyce and American Cultural Conservatism -- 3. Between Marxism and Modernism: Joyce and the Dissident Left -- 4. "On the Side of the Angels": Joyce and the New Critics -- 5. The High Priest of Their Imagination: Joyce and His Catholic Critics -- Conclusion: The Politics of Parallax, or the Transubstantiation of Joyce's Political Soul.
Includes bibliographical references (pages 195-203) and index.
Print version record.
English.
JSTOR
Keywords: Joyce, James, -- 1882-1941.; Joyce, James, -- 1882-1941 -- Appreciation -- United States; Joyce, James, -- 1882-1941; Ulysses (Joyce, James); Politics and literature -- United States -- History -- 20th century; Criticism -- United States -- History -- 20th century; Politique et littérature -- États-Unis -- Histoire -- 20e siècle.; Critique -- États-Unis -- Histoire -- 20e siècle.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Art appreciation; Criticism; Politics and literature; United States; 1900-1999; 20th century; america; american cultural history; banned books; controversy; cultural politics; debates; famous authors; famous novels; feminists; ideological; irish authors; james joyce; joyce scholars; lit students; literary canon; literary criticism; literary critics; literary history; literary theory; literature and culture; modern art and literature; modern history; neo marxists; nonfiction; postmodern lit; poststructuralists; religious issues; ulysses; History